Frame Analysis of Canadian Copyright Reform 2008-2012: From "Made-in-Canada" to a "Balanced Solution" - Rudkin, Aaron (Université d'Ottawa / University of Ottawa, 2014)
From 2008-2012, the Harper government engaged in an effort to reform Canada's copyright legislation. This thesis uses a frame analysis approach to identify two distinct frames advanced by the government during this reform. 2008's Bill C-61 was unsuccessfully framed as a "Made-in-Canada" bill in order to combat opposition claims that American pressure unduly influenced the policy process. Following the failure of this bill, the government embarked on a public consultation on copyright. Although the government did not substantively modify subsequent reform bills, it was able to leverage the consultation process and Supreme Court of Canada jurisprudence to lend legitimacy to its new frame of the reform as a "balanced approach", build a coalition of support, and mitigate opposition. The thesis' analysis supports key conclusions of existing framing literature and creates a space for the role of ideas in the study of copyright reform in Canada.
Keywords: Copyright; Frame analysis; Policy reform; Public consultation; Canada; Digital locks; Intellectual property